IPM action group launched in Kenya - Orondo, Malachi O (Technical Centre for Agricultural and Rural Cooperation, 1997)
Malachi O Orondo, Chair of the Integrated Pest Management (IPM) Action Group, Kenya, wrote to Spore to outline the reasons why the group has been formed. He explained that 'IPM -? is more affordable to small-scale peasants who may not have enough...